Interindividual variability and its impact on the effectiveness of Janus kinase inhibitors in rheumatoid arthritis treatment - Martinez-Molina, Cristina; Vidal, Silvia; Diaz-Torne, Cesar; Park, Hye S.; Corominas, Hèctor (Frontiers in Medicine, 2025)
IntroductionAchieving the primary treat-to-target (T2T) goal in rheumatoid arthritis (RA) remains challenging for many patients, reflecting limitations in the effectiveness of existing treatments. Our study examines factors influencing Janus kinase (JAK) inhibitor effectiveness by analyzing interindividual variability in demographic and clinical characteristics of real-world RA patients.Materials and methodsThis observational retrospective study involves RA patients receiving tofacitinib, baricitinib, upadacitinib, or filgotinib between September 2017 and January 2025. Predictive factors of achieving the T2T goal at 6 months were identified through logistic regression analyses. Disparities in the treatment effectiveness retention based on predictive factors were assessed using the Kaplan–Meier estimate and compared with the log-rank test. The Cox model was applied to analyze whether the predictive factors identified could influence the retention of JAK inhibitor treatment effectiveness.ResultsOne hundred fifty patients were included: 81 (54%) achievers and 69 (46%) non-achievers of remission or, at least, low disease activity at 6 months of treatment. High disease activity at baseline, with respect to moderate activity, was identified as an unfavorable factor for achieving the T2T goal (Odds ratio adjusted: 0.96; 95% confidence interval: 0.92–0.99; p = 0.028). In treatment effectiveness retention rates, no differences were observed between patients with high versus moderate disease activity (p = 0.103). RA disease activity at baseline was not found to impact the survival of JAK inhibitor effectiveness (p = 0.106).ConclusionIn RA, high disease activity at the initiation of treatment with tofacitinib, baricitinib, upadacitinib, or filgotinib does not preclude an effective treatment response but is associated with an increased risk of therapeutic failure. Factors not related to the achievement of the T2T goal at 6 months of JAK inhibitor treatment include: age, female sex, body mass index, RA disease duration, seropositivity for rheumatoid factor, seropositivity for anti-cyclic citrullinated peptides, JAK inhibitor selectivity, type and number of prior biologic treatments, concomitant use and number of prior conventional synthetic disease-modifying antirheumatic drugs, and number of prior JAK inhibitors. These conclusions are derived from a retrospective real-world study and should be confirmed in prospective studies.